Two-dimensional layered nitrogen-doped carbon quantum dot modified carbon nitride loaded in-situ chlorine-doped calcium ferrite nano magnetic composite catalyst and preparation method thereof

The two-dimensional nitrogen-doped carbon quantum dot modified nitrogen-doped iron calcium nanomagnetic composite catalyst addresses the limited ion capacity and oxygen vacancies of existing sharp-stone type iron calcium catalysts, achieving enhanced ozone decomposition and organic pollutant oxidation efficiency by increasing active sites and surface area.

CN119702042AActive Publication Date: 2025-03-28NORTHEAST DIANLI UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411902749.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing sharp-stone type iron calcium catalyst has limited surface oxygen vacancies and ion capacity, which hampers the production of active free radicals during ozone decomposition, resulting in low catalytic activity for ozone oxidation of organic pollutants.

Method used

A two-dimensional nitrogen-doped carbon quantum dot modified nitrogen-doped iron calcium nanomagnetic composite catalyst is developed, specifically Cl-CaFe2O4/g-C3N4/NCQDs, using a sol-gel and hydrothermal method to enhance surface area and active sites, incorporating chlorine doping and nitrogen-doped carbon quantum dots to improve ozone decomposition efficiency.

Benefits of technology

The modified catalyst significantly enhances catalytic activity by providing more active sites and oxygen vacancies, promoting the generation of active free radicals, thereby improving the efficiency of ozone oxidation of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702042A_ABST
    Figure CN119702042A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional layered nitrogen-doped carbon quantum dot modified carbon nitride loaded in-situ chlorine-doped calcium ferrite nano magnetic composite catalyst and a preparation method thereof, relates to the technical field of water treatment materials, and aims to solve the problems that the number of oxygen vacancies on the surface of an existing spinel type calcium ferrite catalyst is small, the number of contained anions and cations is limited, and the service life of the existing spinel type calcium ferrite catalyst is short. The ozone decomposition cannot be effectively promoted to generate active free radicals, so that the catalytic activity of the catalyst is low. The two-dimensional layered nitrogen-doped carbon quantum dot modified carbon nitride loaded in-situ chlorine-doped calcium ferrite nano magnetic composite catalyst is prepared by combining a sol-gel method and a hydrothermal method, the chemical equation of the catalyst is Cl-CaFe2O4 / g-C3N4 / NCQDs, and compared with CaFe2O4, the catalytic activity is obviously enhanced, the surface area is larger, and the preparation method is simple and convenient. More active sites and oxygen vacancies are provided, and ozone can be promoted to generate more active free radicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment materials, and in particular to a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-loaded in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and a preparation method thereof. Background Art

[0002] Antibiotics are widely used to treat diseases in humans and livestock. After a large amount of antibiotics enter the environment, they are difficult to remove through traditional wastewater treatment processes due to their inherent antibacterial properties. Norfloxacin (NOR) belongs to the fluoroquinolone antibiotic class. Trace levels of norfloxacin have potential adverse effects on aquatic wildlife, ecosystems, and human health, and may lead to the emergence of antibiotic-resistant bacteria.

[0003] Catalytic ozonation technology uses catalysts to accelerate the production of active free radicals by ozone, and mineralizes refractory organic pollutants into H2O and CO2. Heterogeneous catalysts mainly include precious metal catalysts, transition metal catalysts, alkaline earth metal catalysts and non-metallic catalysts. Among them, precious metal catalysts have strong catalytic performance, good stability and long life, but they are expensive and difficult to recycle. The dissolution of heavy metal ions into the solution will also cause secondary pollution, which limits their application and development in catalytic ozonation degradation of organic pollutants. Transition metal oxides mainly include oxides such as iron, cobalt, and nickel. Because the d electron layer of their metal cations easily gains and loses electrons, they have strong redox properties. Most transition metal oxides have good stability, low preparation cost and convenient recycling. However, compared with transition metal oxides, spinel oxides are more stable. Among them, spinel CaFe2O4 catalysts are mainly used in the fields of photocatalysis and electrocatalysis, and there are few studies on their application in catalytic ozonation. The main reason is that there are few oxygen vacancies on its surface, and the number of anions and cations that can be accommodated is limited. It cannot more effectively promote the decomposition of ozone to produce active free radicals, so the degradation efficiency of organic wastewater is low. In order to improve the efficiency of CaFe2O4 catalyst in catalyzing the ozonation of organic wastewater, it is necessary to provide more oxygen vacancies and active sites on its surface to receive more anions and cations and promote the decomposition of ozone to produce more active free radicals.

[0004] Therefore, the existing technology needs to be further improved and perfected. Summary of the invention

[0005] The technical problems to be solved by the present invention are:

[0006] The existing spinel calcium ferrite catalyst has a small number of oxygen vacancies on its surface and can accommodate a limited number of anions and cations, which cannot more effectively promote the decomposition of ozone to produce active free radicals, resulting in low catalytic activity of the catalyst.

[0007] The present invention adopts the following technical solutions to solve the above technical problems:

[0008] The present invention provides a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst. The catalyst is a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst. The chemical formula of the catalyst is Cl-CaFe2O4 / g-C3N4 / NCQDs.

[0009] The present invention provides a method for preparing a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst, comprising the following steps:

[0010] 1. Prepare precursor solution A: dissolve calcium nitrate and ferric nitrate in deionized water, stir until completely dissolved, then add citric acid and calcium chloride, stir evenly, to obtain precursor solution A;

[0011] 2. Preparing sol B: heating and stirring the precursor solution A to prepare sol B;

[0012] 3. Preparation of gel C: drying sol B to obtain gel C;

[0013] 4. Preparation of carbon nitride (g-C3N4): calcining melamine to obtain g-C3N4 powder;

[0014] 5. Preparation of N-doped carbon quantum dots (NCQDs): Add citric acid and urea to deionized water for hydrothermal reaction to obtain NCQDs;

[0015] 6. Preparation of Cl-CaFe2O4 / g-C3N4 (CCG): Gel C and g-C3N4 powder were fully mixed in an agate mortar to obtain a mixture, and the mixture was calcined to obtain Cl-CaFe2O4 / g-C3N4 (CCG);

[0016] 7. Preparation of the ternary composite material Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD): Add CCG and NCQDs to deionized water in proportion, stir to mix, and carry out a hydrothermal reaction. Filter the precipitate, wash the precipitate with ethanol and deionized water, and dry to obtain the Cl-CaFe2O4 / g-C3N4 / NGQDs (CCGD) catalyst.

[0017] Furthermore, in step 1, the molar ratio of calcium nitrate, ferric nitrate, citric acid and calcium chloride is (0.5-1):(1-3):(3-6):(0.1-0.5).

[0018] Furthermore, in step 4, the calcination temperature of melamine is not less than 500°C.

[0019] Furthermore, in step five, the molar ratio of citric acid to urea is (1-3):1.

[0020] Furthermore, the hydrothermal reaction conditions in step five are 160-200° C. for 6 h to 10 h.

[0021] Furthermore, in step six, the mass ratio of gel C to g-C3N4 is (1-4):1.

[0022] Furthermore, the calcination temperature of the mixture in step six is ​​not less than 800°C.

[0023] Furthermore, the hydrothermal reaction conditions in step seven are 160-200° C. for 6 h to 10 h.

[0024] Furthermore, the drying condition in step seven is drying at 60-120° C. for 6 h to 10 h.

[0025] Furthermore, the ratio of CCG to NCQDs in step seven is 1 g: (3-6) mL.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention adopts a sol-gel method and a hydrothermal method to prepare a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-loaded in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst. Compared with CaFe2O4, the catalytic activity is significantly enhanced, the catalyst has a larger surface area, and more active sites and oxygen vacancies are provided, thereby promoting ozone to produce more active free radicals.

[0028] The present invention adopts citric acid with strong reducing property as a complexing agent. After the solvent evaporates, the solution is viscous, and the complex molecules are close to each other and connected by hydrogen bonds to form a gel. Through the induction of anionic chlorine, the anionic component is enhanced without changing the spatial structure, thereby improving the structural stability and conductivity of the catalyst. During the coupling process of carbon nitride and calcium ferrite, the electron-hole pairs are separated by inhibiting the heterojunction, and the holes in the valence band of carbon nitride are enriched in large quantities and react with ozone to generate more active free radicals, so as to enhance the catalytic activity of the catalyst. The addition of carbon quantum dots affects the shape and conductivity of calcium ferrite, induces the crystal to produce intrinsic defects, provides more active sites and oxygen vacancies, is conducive to the electron transfer in the catalytic reaction process, and generates a large amount of surface active oxygen. Due to the charge redistribution induced by nitrogen, the nitrogen-doped carbon quantum dots have higher catalytic activity in redox reactions, are very easy to disperse and aggregate in water, and can form an effective and stable catalyst with calcium ferrite. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1Schematic diagram of the electron transfer process of the two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst in an embodiment of the present invention;

[0030] Figure 2 This is a scanning electron microscope image of a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst in an embodiment of the present invention;

[0031] Figure 3 This is an XRD pattern of the two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst in an embodiment of the present invention;

[0032] Figure 4 This is the XPS spectrum of the two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the scheme of the present invention, exemplary implementations or embodiments of the present invention will be described below in conjunction with the accompanying drawings. Obviously, the described implementations or embodiments are only implementations or embodiments of a part of the present invention, not all of them. Based on the implementations or embodiments of the present invention, all other implementations or embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0035] The present invention provides a method for preparing a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst, comprising the following steps:

[0036] 1. Prepare precursor solution A: dissolve calcium nitrate and ferric nitrate in deionized water, stir until completely dissolved, then add citric acid and calcium chloride, stir evenly, to obtain precursor solution A;

[0037] 2. Preparing sol B: heating and stirring the precursor solution A to prepare sol B;

[0038] 3. Preparation of gel C: drying sol B to obtain gel C;

[0039] 4. Preparation of carbon nitride (g-C3N4): calcining melamine to obtain g-C3N4 powder;

[0040] 5. Preparation of N-doped carbon quantum dots (NCQDs): Add citric acid and urea to deionized water for hydrothermal reaction to obtain NCQDs;

[0041] 6. Preparation of Cl-CaFe2O4 / g-C3N4 (CCG): Gel C and g-C3N4 powder were fully mixed in an agate mortar to obtain a mixture, and the mixture was calcined to obtain Cl-CaFe2O4 / g-C3N4 (CCG);

[0042] 7. Preparation of a ternary composite material Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD): Add CCG and NCQDs to deionized water in proportion, stir to mix, and perform a hydrothermal reaction. Filter the precipitate, wash the precipitate with ethanol and deionized water, and dry to obtain a Cl-CaFe2O4 / g-C3N4 / NGQDs (CCGD) catalyst, the chemical formula of the catalyst being Cl-CaFe2O4 / g-C3N4 / NCQDs.

[0043] In one embodiment of the present invention, in step 1, the molar ratio of calcium nitrate, ferric nitrate, citric acid and calcium chloride is preferably (0.5-1):(1-3):(3-6):(0.1-0.5).

[0044] In order to allow melamine to fully react to form g-C3N4, the calcination temperature of melamine in the above step 4 is preferably not less than 500°C.

[0045] In one embodiment of the present invention, in step five, the molar ratio of citric acid to urea is preferably (1-3):1.

[0046] In order to allow citric acid and urea to react fully, the hydrothermal reaction conditions in step 5 are 160-200° C. for 6 h to 10 h.

[0047] In one embodiment of the present invention, in step six, the mass ratio of gel C to g-C3N4 is preferably (1 to 4):1.

[0048] In one embodiment of the present invention, the calcination temperature of the mixture in step six is ​​preferably not less than 800°C.

[0049] In order to fully react CCG and NCQDs, the hydrothermal reaction conditions in step seven are 160-200°C for 6h-10h.

[0050] In one embodiment of the present invention, in step seven, the ratio of CCG to NCQDs is preferably 1 g: (3-6) mL.

[0051] The beneficial effects of the present invention will be described below in conjunction with specific embodiments and comparative examples.

[0052] Example 1: A method for preparing a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst is specifically completed by the following steps:

[0053] 1. Prepare precursor solution A: dissolve 0.005 mol calcium nitrate and 0.02 mol ferric nitrate in 100 ml deionized water, stir at 40°C until the solid is completely dissolved, then add 0.04 mol citric acid and 0.005 mol calcium chloride, and stir evenly until completely dissolved to obtain precursor solution A;

[0054] 2. Preparation of Sol B: Place solution A in a constant temperature water bath at 85°C and stir for 2 hours to obtain Sol B;

[0055] 3. Preparation of gel C: drying sol B in a constant temperature drying oven at 120°C to obtain gel C;

[0056] 4. Preparation of carbon nitride (g-C3N4): 10 g of melamine was calcined in a muffle furnace at 550 °C for 4 h to obtain yellow powder g-C3N4;

[0057] 5. Preparation of N-doped carbon quantum dots (NCQDs): 0.02 mol of citric acid and 0.01 mol of urea were dissolved in 100 ml of deionized water and subjected to hydrothermal reaction at 180 °C for 6 h to obtain NCQDs;

[0058] 6. Preparation of Cl-CaFe2O4 / g-C3N4 (CCG): 2 g of gel C and 0.5 g of g-C3N4 were fully mixed in an agate mortar for 15 min; the resulting mixture was calcined at 850°C for 4 h to form Cl-CaFe2O4 / g-C3N4 (CCG);

[0059] 7. Preparation of the ternary composite material Cl-CaFe2O4 / g-C3N4 / NCQDs: Add 1 g CCG and 5 mL NCQDs solution to 50 mL deionized water, stir for 2 h, and keep warm at 180 °C in a polytetrafluoroethylene-lined high-pressure reactor for 6 h. Filter the precipitate, wash it alternately with ethanol and deionized water for 3 times, and dry it at 90 °C for 8 h to obtain a reddish-brown magnetic powder Cl-CaFe2O4 / g-C3N4 / NCQDs catalyst.

[0060] The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst obtained in Example 1 was subjected to scanning electron microscopy. Figure 2 As shown, it can be seen that the two-dimensional layered nitrogen-doped carbon quantum dots modified carbon nitride supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst obtained in Example 1 has a two-dimensional layered structure.

[0061] The two-dimensional layered nitrogen-doped carbon quantum dots modified carbon nitride supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst obtained in Example 1 was characterized by XRD. Figure 3 As shown, it can be seen that the catalyst retains the original spinel structure basis.

[0062] The Cl-CaFe2O4 / g-C3N4 / NCQDs catalyst obtained in Example 1 was subjected to XPS spectrum detection. Figure 4 As shown, the Ca element in the Cl-CaFe2O4 / g-C3N4 / NCQDs catalyst obtained in Example 1 is Ca 2+ , Fe element is Fe 3+ and Fe 2 + , indicating that electron transfer occurs on the surface of Cl-CaFe2O4 / g-C3N4 / NCQDs catalyst and oxygen vacancies are generated, which is beneficial to improving the catalytic performance; a chlorine peak can be detected in the XPS spectrum of Cl-CaFe2O4 / g-C3N4 / NCQDs catalyst, indicating that chlorine has been successfully doped into calcium ferrite crystals.

[0063] Embodiment 2: The difference between this embodiment and embodiment 1 is that:

[0064] 1. Prepare precursor solution A: Dissolve 0.01 mol calcium nitrate and 0.03 mol ferric nitrate in 100 ml deionized water, stir at 40°C until the solid is completely dissolved, then add 0.05 mol citric acid and 0.001 mol calcium chloride, and stir evenly until completely dissolved to obtain precursor solution A.

[0065] Embodiment 3: The difference between this embodiment and embodiment 1 is that:

[0066] 1. Prepare precursor solution A: Dissolve 0.01 mol calcium nitrate and 0.01 mol ferric nitrate in 100 ml deionized water, stir at 40°C until the solid is completely dissolved, then add 0.03 mol citric acid and 0.001 mol calcium chloride, and stir evenly until completely dissolved to obtain precursor solution A.

[0067] Embodiment 4: The difference between this embodiment and embodiment 1 is that:

[0068] 5. Preparation of N-doped carbon quantum dots (NCQDs): Dissolve 0.01 mol of citric acid and 0.01 mol of urea in 100 ml of deionized water and perform hydrothermal reaction at 180° C. for 6 h to obtain NCQDs.

[0069] Embodiment 5: The difference between this embodiment and embodiment 1 is that:

[0070] 5. Preparation of N-doped carbon quantum dots (NCQDs): 0.03 mol citric acid and 0.01 mol urea were dissolved in 100 ml of deionized water and subjected to hydrothermal reaction at 180° C. for 6 h to obtain NCQDs.

[0071] Embodiment 5: The difference between this embodiment and the embodiment is that,

[0072] 6. Preparation of Cl-CaFe2O4 / g-C3N4 (CCG): 1 g of gel C and 0.5 g of g-C3N4 were fully mixed in an agate mortar for 15 min. The resulting mixture was calcined at 850°C for 4 h to form Cl-CaFe2O4 / g-C3N4 (CCG).

[0073] Embodiment 6: The difference between this embodiment and the embodiment is that,

[0074] 6. Preparation of Cl-CaFe2O4 / g-C3N4 (CCG): 1.5 g of gel C and 0.5 g of g-C3N4 were mixed thoroughly in agate mortar for 15 min. The resulting mixture was calcined at 850 °C for 4 h to form Cl-CaFe2O4 / g-C3N4 (CCG).

[0075] Embodiment 7: The difference between this embodiment and the embodiment is that,

[0076] 6. In the process of preparing Cl-CaFe2O4 / g-C3N4(CCG), 0.5g of gel C and 0.5g of g-C3N4 were mixed in agate mortar for 15min. The obtained mixture was calcined at 850℃ for 4h to form Cl-CaFe2O4 / g-C3N4(CCG).

[0077] Embodiment 8: The difference between this embodiment and embodiment 1 is that:

[0078] 7. Preparation of the ternary composite material Cl-CaFe2O4 / g-C3N4 / NCQDs: Add 1 g CCG and 3 mL NCQDs solution to 50 mL deionized water, stir for 2 h, and keep warm at 180 °C in a polytetrafluoroethylene-lined high-pressure reactor for 6 h. Filter the precipitate, wash it alternately with ethanol and deionized water for 3 times, and dry it at 90 °C for 8 h to obtain a reddish-brown magnetic powder Cl-CaFe2O4 / g-C3N4 / NCQDs catalyst.

[0079] Embodiment 9: The difference between this embodiment and embodiment 1 is that:

[0080] 7. Preparation of the ternary composite material Cl-CaFe2O4 / g-C3N4 / NCQDs: Add 1 g CCG and 6 mL NCQDs solution to 50 mL deionized water, stir for 2 h, and keep warm at 180 °C in a polytetrafluoroethylene-lined high-pressure reactor for 6 h. Filter the precipitate, wash it alternately with ethanol and deionized water for 3 times, and dry it at 90 °C for 8 h to obtain a reddish-brown magnetic powder Cl-CaFe2O4 / g-C3N4 / NCQDs catalyst.

[0081] Embodiment 10: The difference between this embodiment and embodiment 1 is that:

[0082] 3. Preparation of gel C: drying sol B in a constant temperature drying oven at 80°C to obtain gel C;

[0083] Embodiment 11: The difference between this embodiment and embodiment 1 is that:

[0084] The hydrothermal reaction conditions in step seven are 160° C. for 10 h.

[0085] Embodiment 12: The difference between this embodiment and embodiment 1 is that:

[0086] The hydrothermal reaction conditions in step seven are 200° C. for 6 h.

[0087] Embodiment 13: The difference between this embodiment and embodiment 1 is that:

[0088] The drying condition in step seven is drying at 60° C. for 10 h.

[0089] Embodiment 14: The difference between this embodiment and embodiment 1 is that:

[0090] The drying condition in step seven is drying at 120° C. for 8 h.

[0091] Comparative Example 1: A method for preparing a Cl-CaFe2O4 (CCF) catalyst is specifically prepared by the following steps:

[0092] 1. Prepare precursor solution A. Dissolve 0.005 mol calcium nitrate and 0.02 mol ferric nitrate in 100 ml deionized water, stir for 30 min at 40°C (solid is completely dissolved), then add 0.04 mol citric acid and 0.005 mol calcium chloride, and stir evenly until completely dissolved to obtain precursor solution A;

[0093] 2. Preparation of Sol B. Place solution A in a constant temperature water bath at 85°C and stir for 2 hours to obtain Sol B;

[0094] 3. Preparation of gel C: drying the obtained sol B in a constant temperature drying oven at 120° C. to obtain gel C;

[0095] 4. Preparation of Cl-CaFe2O4 (CCF): Gel C was calcined at 850°C for 4 hours to form Cl-CaFe2O4 (CCF) catalyst.

[0096] Comparative Example 2: The preparation method of Cl-CaFe2O4 / g-C3N4 (CCG) catalyst is specifically completed according to the following steps:

[0097] 1. Prepare precursor solution A. Dissolve 0.005 mol calcium nitrate and 0.02 mol ferric nitrate in 100 ml deionized water, stir for 30 min at 40°C (solid is completely dissolved), then add 0.04 mol citric acid and 0.005 mol calcium chloride, and stir evenly until completely dissolved to obtain precursor solution A;

[0098] 2. Preparation of Sol B. Place solution A in a constant temperature water bath at 85°C and stir for 2 hours to obtain Sol B;

[0099] 3. Preparation of gel C. Dry the obtained sol B in a constant temperature drying oven at 120°C to obtain gel C;

[0100] 4. Preparation of carbon nitride (g-C3N4): 10 g of melamine was calcined in a muffle furnace at 550°C for 4 h to obtain yellow powder g-C3N4;

[0101] 5. Preparation of Cl-CaFe2O4 / g-C3N4 (CCG). 2 g of gel C and 0.5 g of g-C3N4 were fully mixed in an agate mortar for 15 min. The resulting mixture was calcined at 850°C for 4 h to obtain a Cl-CaFe2O4 / g-C3N4 (CCG) catalyst.

[0102] Comparative Example 3

[0103] 1L of norfloxacin wastewater with a concentration of 20mg / L was placed in a glass reactor, and ozone with a concentration of 1.24mg / L and a flow rate of 1000mg / min was introduced for 2min; the wastewater was treated with ozonation alone for 60min, and 10mL was sampled every 10min using a peristaltic pump. After filtering through a 0.22μm filter membrane, the residual norfloxacin concentration in the wastewater was detected by ultraviolet spectrophotometry at 278nm. The degradation curve of norfloxacin wastewater was drawn based on the detection data, and the removal rate was calculated.

[0104] Embodiment 15

[0105] 1. Place 1L of 20mg / L norfloxacin wastewater in a glass reactor, introduce ozone at a concentration of 1.24mg / L and a flow rate of 1000mg / min for 2min; add 0.1g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 1;

[0106] 2. Continue catalytic ozonation treatment for 60 minutes, use a peristaltic pump to sample 10 mL every 10 minutes, filter through a 0.22 μm filter membrane, and use ultraviolet spectrophotometry to detect the remaining norfloxacin concentration in the wastewater at 278 nm. Draw the degradation curve of norfloxacin wastewater based on the test data, and calculate the removal rate. Magnetic recovery is carried out after the catalyst ozonation treatment is completed.

[0107] Example 16: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 2 is added in step one.

[0108] Example 17: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 3 is added in step 1.

[0109] Example 18: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 4 is added in step 1.

[0110] Example 19: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 5 is added in step one.

[0111] Example 20: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 6 is added in step one.

[0112] Example 21: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 7 is added in step one.

[0113] Example 22: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 8 is added in step one.

[0114] Example 23: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 9 is added in step one.

[0115] Example 24: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 10 is added in step one.

[0116] Example 25: The difference between this example and Example 15 is that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 11 is added in step one.

[0117] Example 26: This example differs from Example 15 in that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 12 is added in step one.

[0118] Example 27: The difference between this example and Example 15 is that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 13 is added in step one.

[0119] Example 28: The difference between this example and Example 15 is that 0.1 g of the Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD) catalyst prepared in Example 14 is added in step one.

[0120] Comparative Example 4: This embodiment differs from Embodiment 5 in that 0.1 g of the Cl-CaFe2O4 (CF) catalyst prepared in Comparative Example 1 is added in step 1.

[0121] Comparative Example 5: The difference between this example and Example 5 is that 0.1 g of the Cl-CaFe2O4 / g-C3N4 (CCG) catalyst prepared in Comparative Example 2 is added in step 1.

[0122] The norfloxacin removal rate (%) results obtained by Examples 15-28 and Comparative Examples 3-5 are summarized as shown in Table 1. It can be seen that the norfloxacin removal rate in Example 15 reaches 70.04% after 60 minutes of catalytic ozonation treatment, which is 31.66% higher than the ozone removal rate of Comparative Example 3, and is significantly improved compared with the Cl-CaFe2O4 of Comparative Example 4 and the Cl-CaFe2O4 / g-C3N4 phase of Comparative Example 5, indicating that the induction of chloride ions in the catalyst, the coupling of carbon nitride and spinel calcium ferrite, and the composite of nitrogen-doped carbon quantum dots are beneficial to improving the catalytic performance.

[0123] Table 1

[0124] 10(min) 20(min) 30(min) 40(min) 50(min) 60(min) Embodiment 15 17.15 30.17 44.35 52.43 62.92 70.04 Example 16 13.92 23.45 34.48 42.01 53.64 58.54 Embodiment 17 13.98 23.12 33.75 41.87 52.32 57.43 Embodiment 18 14.35 24.55 39.01 50.55 60.12 67.68 Embodiment 19 14.2 24.27 38.37 49.55 59.53 67.59 Embodiment 20 14.81 26.07 36.66 45.38 57.37 63.04 Embodiment 21 14.07 24.02 36.94 47.37 55.02 60.95 Embodiment 22 14.41 24.67 39.33 50.98 60.34 67.77 Embodiment 23 14.31 24.45 38.56 50.01 59.92 67.54 Embodiment 24 16.92 29.76 42.98 51.12 62.03 69.53 Embodiment 25 14.52 24.71 40.01 50.03 60.42 68.02 Embodiment 26 14.61 24.82 40.13 50.12 60.51 68.21 Embodiment 27 15.11 26.04 41.76 50.54 61.24 68.98 Embodiment 28 16.05 27.43 42.23 50.98 61.67 69.01 Comparative Example 3 9.3 14.5 21.51 28.45 33.24 38.38 Comparative Example 4 12.55 17.88 30.08 36.4 41.73 50.49 Comparative Example 5 13.84 22.99 33.45 41.69 49.29 53.77

[0125] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

[0126] Working principle:

[0127] like Figure 1 As shown, the present invention reduces the oxidation of calcium and chlorine leaching in calcium ferrite by in-situ doping with chloride ions, enhances the anion component without changing the spatial structure of calcium ferrite, and improves its structural stability and conductivity. Halogen chlorine has a lower electronegativity than oxygen, and after doping, it can enhance the metal-oxygen covalent bond, which is beneficial to the electron transfer in the catalytic process; the electrochemical potential of the original catalyst is reduced by chlorine substitution, forming an in-situ doped metal oxide (hydroxide) phase, making the catalytic reaction easier to carry out and the catalyst activity higher.

[0128] During the coupling process between carbon nitride and calcium ferrite, electron-hole pairs are separated by inhibiting the heterojunction, and holes in the valence band of carbon nitride are enriched in large quantities, and react with ozone to generate more active free radicals, thereby enhancing the catalytic activity of the catalyst. The addition of carbon quantum dots affects the shape and conductivity of calcium ferrite, induces intrinsic defects in the crystal, provides more active sites and oxygen vacancies, is conducive to electron transfer during the catalytic reaction, and generates a large amount of surface active oxygen. Due to the nitrogen-induced charge redistribution, nitrogen-doped carbon quantum dots have higher catalytic activity in redox reactions, are extremely easy to disperse and aggregate in water, and can form a stable catalyst with calcium ferrite for effective removal of norfloxacin in aqueous solution.

Claims

1. A two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst, characterized in that: The catalyst is a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst, and the chemical formula of the catalyst is Cl-CaFe2O4 / g-C3N4 / NCQDs.

2. A method for preparing a two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst, characterized in that: The steps include:

1. Prepare precursor solution A: dissolve calcium nitrate and ferric nitrate in deionized water, stir until completely dissolved, then add citric acid and calcium chloride, stir evenly, to obtain precursor solution A; 2. Preparing sol B: heating and stirring the precursor solution A to prepare sol B; 3. Preparation of gel C: drying sol B to obtain gel C; 4. Preparation of carbon nitride (g-C3N4): calcining melamine to obtain g-C3N4 powder; 5. Preparation of N-doped carbon quantum dots (NCQDs): Add citric acid and urea to deionized water for hydrothermal reaction to obtain NCQDs; 6. Preparation of Cl-CaFe2O4 / g-C3N4 (CCG): Gel C and g-C3N4 powder were fully mixed in an agate mortar to obtain a mixture, and the mixture was calcined to obtain Cl-CaFe2O4 / g-C3N4 (CCG); 7. Preparation of the ternary composite material Cl-CaFe2O4 / g-C3N4 / NCQDs (CCGD): Add CCG and NCQDs to deionized water in proportion, stir to mix, and carry out a hydrothermal reaction. Filter the precipitate, wash the precipitate with ethanol and deionized water, and dry to obtain the Cl-CaFe2O4 / g-C3N4 / NGQDs (CCGD) catalyst.

3. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 2, characterized in that: In step 1, the molar ratio of calcium nitrate, ferric nitrate, citric acid and calcium chloride is (0.5-1):(1-3):(3-6):(0.1-0.5).

4. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 3, characterized in that: The calcination temperature of melamine in step 4 is not less than 500°C.

5. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 4, characterized in that: In step 5, the molar ratio of citric acid to urea is (1-3):

1.

6. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 5, characterized in that: The conditions of the hydrothermal reaction in step 5 are 160-200° C. for 6 h to 10 h.

7. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 6, characterized in that: The mass ratio of gel C to g-C3N4 in step six is ​​(1~4):

1.

8. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 7, characterized in that: The calcination temperature of the mixture in step six is ​​not less than 800°C.

9. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 8, characterized in that: The conditions of the hydrothermal reaction in step seven are to react at 160-200° C. for 6 h to 10 h.

10. The two-dimensional layered nitrogen-doped carbon quantum dot-modified carbon nitride-supported in-situ chlorine-doped calcium ferrite nanomagnetic composite catalyst and its preparation method according to claim 9, characterized in that: The ratio of CCG and NCQDs in step 7 is 1 g: (3-6) mL.

Citation Information

Patent Citations

  • Preparation of carbon quantum dot doped carbon nitride catalyst and application of carbon quantum dot doped carbon nitride catalyst in non-photocatalytic degradation of dye wastewater

    CN115920938A

  • Preparation method and application of magnetic all-solid Z-type ternary heterojunction photo-Fenton catalyst

    CN117482979A

  • Preparation method of carbon nitride / wood-based charcoal / magnesium ferrite photocatalyst capable of efficiently reducing Cr (VI)

    CN118454717A